2021
DOI: 10.1063/5.0058093
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of TiOx/Sb2Se3/p-NiOx photocathode for efficient photoelectrochemical water reduction

Abstract: Photoelectrochemical (PEC) water splitting directly converts solar energy into clean and sustainable hydrogen energy, representing a promising and effective technique for solving the world's energy crisis. A hole transfer layer (HTL) plays a vital role for extracting holes from a semiconductor layer to a back electrode in PEC cells for water splitting. In this work, a TiOx/Sb2Se3/NiOx photocathode was fabricated by using p-NiOx as HTL. We show that the electrical properties of NiOx films can be well adjusted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In addition, the work function of Mo is close to the conduction band minimum (CBM) of Sb 2 Se 3 , which makes it easy to form the recombination center . Meanwhile, Lee et al reported that Cu-doped NiO x as a hole-selective layer for Sb 2 Se 3 obtained a photocurrent density of 17.5 mA cm –2 at 0 V RHE , and the preparation of NiO x by pulsed laser deposition as the hole transport layer (HTL) of the Sb 2 Se 3 photocathode has been reported by our group, but the low conductivity of nickel oxide is not favorable for the hole transfer …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the work function of Mo is close to the conduction band minimum (CBM) of Sb 2 Se 3 , which makes it easy to form the recombination center . Meanwhile, Lee et al reported that Cu-doped NiO x as a hole-selective layer for Sb 2 Se 3 obtained a photocurrent density of 17.5 mA cm –2 at 0 V RHE , and the preparation of NiO x by pulsed laser deposition as the hole transport layer (HTL) of the Sb 2 Se 3 photocathode has been reported by our group, but the low conductivity of nickel oxide is not favorable for the hole transfer …”
Section: Introductionmentioning
confidence: 87%
“…19 Meanwhile, Lee et al reported that Cu-doped NiO x as a holeselective layer for Sb 2 Se 3 obtained a photocurrent density of 17.5 mA cm −2 at 0 V RHE , 18 and the preparation of NiO x by pulsed laser deposition as the hole transport layer (HTL) of the Sb 2 Se 3 photocathode has been reported by our group, but the low conductivity of nickel oxide is not favorable for the hole transfer. 20 As a p-type semiconductor, copper antimony sulfide (CuSbS 2 ) is an emerging material for PEC cells because of its suitable band gap and high optical absorption coefficent. 21 Furthermore, it is made of low-cost, low-toxicity, and Earthabundant elements.…”
Section: Introductionmentioning
confidence: 99%
“…[63] The second type of the photocathode hole transport system (Figure 5b) mainly consists of a conductive substrate, a HTL, a photocatalyst, and a hydrogen evolution cocatalyst. [73][74][75][76][77][78][79][80][81] For an unstable photocatalytic systems, a protective layer is often added between the photocatalyst and the cocatalyst. [73,76,77] Furthermore, most of the cocatalysts in this system are platinum, which not only provides surface redox sites and increases hydrogen production, but also collects electrons and promotes carrier transport.…”
Section: Structure Of Photocathode Htlmentioning
confidence: 99%
“…[73][74][75][76][77][78][79][80][81] For an unstable photocatalytic systems, a protective layer is often added between the photocatalyst and the cocatalyst. [73,76,77] Furthermore, most of the cocatalysts in this system are platinum, which not only provides surface redox sites and increases hydrogen production, but also collects electrons and promotes carrier transport. [73,74,[76][77][78] Under illumination, the photogenerated holes are transferred from the VB of photocatalyst to the counter electrode through the conductive glass and external circuit for water oxidation.…”
Section: Structure Of Photocathode Htlmentioning
confidence: 99%
See 1 more Smart Citation